Thrombolytic Therapy in Acute Ischemic Stroke - Hacke, Werner; Zoppo, Gregory J. del; Hirschberg, Matthias (Springer Berlin Heidelberg, 1991)
During the last decade scientists in both basic and clinical research have renew ed their interest in the potential role of thrombolytic therapy in the treatment of acute ischemic stroke. The reevaluation of this approach was kindled by our growing knowledge of the pathogenesis of thrombotic and embolic stroke and by the development of new thrombolytic agents. With no proven therapy for acute ischemic stroke available, the potential value of early pharmacologic recanalization of occluded vessels in the management of acute stroke patients - an approach that has been supported by animal experiments and a limited number of uncontrolled clinical pilot studies - is again under scrutiny. A sym posium on "Thrombolysis in Acute Cerebral Ischemia" was held in Heidel berg, Germany, in May 1990 to summarize and discuss the pathophysiological background for thrombolysis in acute ischemic stroke and the recent ex perimental and clinical experience with the new generation of thrombolytic agents. The editors are fortunate to be able to include authoritative manuscripts from almost all the speakers at the symposium. These include reports of work by the most active investigators in this challenging field. The editors wish to express their gratitude to all the contributors for the additional work they have undertaken. Additionally, we would like to thank Springer-Verlag, Heidelberg, for its generous assistance in the preparation and rapid publication of this volume. Heidelberg, August 1990 WERNER HACKE GREGORY J. DEL ZopPO MATTHIAS HIRSCHBERG Contents I.